2003
DOI: 10.1046/j.1364-3703.2003.00186.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic HSP90 and HSP70 are essential components of INF1‐mediated hypersensitive response and non‐host resistance toPseudomonas cichoriiinNicotiana benthamiana

Abstract: SUMMARY Mitogen-activated protein kinases (MAPKs) play pivotal roles in the signal transduction pathway of plant defence responses against pathogens. A search for MAPK-interacting proteins revealed an interaction between a Nicotiana benthamiana MAPK, SIPK (NbSIPK) and cytosolic Hsp90 (NbHsp90c-1) in yeast two-hybrid assay. To study the function of Hsp90 in disease resistance, we silenced NbHsp90c-1 in N. benthamiana by virus-induced gene silencing (VIGS) with Potato virus X (PVX). NbHsp90c-1 silenced plants ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
158
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(168 citation statements)
references
References 26 publications
6
158
0
4
Order By: Relevance
“…Among the mutants with defects in the salicylic acid (SA) signal transduction pathway, nonhost resistance was diminished in eds1 mutants and transgenic plants with the bacterial NahG gene relative to wild-type plants (Parker et al, 1996;Mellersh and Heath, 2003;Yun et al, 2003;Zimmerli et al, 2004). Using virus-induced gene silencing, the chaperone and chaperone-like proteins HSP70, HSP90, and SGT1, which are thought to stabilize resistance (R) proteins and act upstream of EDS1, were shown to contribute to nonhost resistance in Nicotiana benthamiana (Peart et al, 2002;Kanzaki et al, 2003). Mutants with defects in the ethylene/jasmonate (ET/ JA) signal transduction pathways exhibited wild-type levels of nonhost resistance in Arabidopsis thaliana, even though there is evidence from microarray studies that this pathway is preferentially induced after inoculation of plants with some inappropriate pathogens (Huitema et al, 2003;Zimmerli et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Among the mutants with defects in the salicylic acid (SA) signal transduction pathway, nonhost resistance was diminished in eds1 mutants and transgenic plants with the bacterial NahG gene relative to wild-type plants (Parker et al, 1996;Mellersh and Heath, 2003;Yun et al, 2003;Zimmerli et al, 2004). Using virus-induced gene silencing, the chaperone and chaperone-like proteins HSP70, HSP90, and SGT1, which are thought to stabilize resistance (R) proteins and act upstream of EDS1, were shown to contribute to nonhost resistance in Nicotiana benthamiana (Peart et al, 2002;Kanzaki et al, 2003). Mutants with defects in the ethylene/jasmonate (ET/ JA) signal transduction pathways exhibited wild-type levels of nonhost resistance in Arabidopsis thaliana, even though there is evidence from microarray studies that this pathway is preferentially induced after inoculation of plants with some inappropriate pathogens (Huitema et al, 2003;Zimmerli et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In animals, HSP70s exert activities in processes such as oncogenesis, neurodegenerative and autoimmune diseases and viral infections [20][21][22]. In plants, it was reported that HSP70 and HSP90 are essential components in the INF1-mediated hypersensitive response in Nicotiana benthamiana, and that they function upstream or independent of the MAPK cascade [23]. Moreover, various reports describe that HSP70 expression in plants is induced upon infection with pathogens [23][24][25][26], but more detailed analysis of HSP70 expression profiles during plant-pathogen interactions are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…So far, genetic approaches have identified relatively few components required for R gene function in plants [5]. A highly conserved protein class, the heat-shock proteins, has now been added to the list and work on these proteins promises to provide fresh insights to the molecular mechanics of the pathogen recognition process [6][7][8][9].…”
mentioning
confidence: 99%